(untitled) (Confluenţe Bibliologice, 2023)
The article presents the analysis of three books on the history of Bessarabia written by Nicolae Iorga in the work „The Romanian Nation from Bessarabia": I. H. Zucker „Bessarabia. Observations and reflections", I. G. Kolh, „Reisen in Sudrussland" and Dumitru C. Moruzzi, „ Bessarabia and its past (1712-1905)".